GAME-BASED READING INSTRUCTION IN EARLY GRADES - Tashmatova Mahira Takhirovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Game-based reading instruction has become one of the most effective approaches in modern primary education. Early grade learners require engaging and interactive methods that support literacy development while maintaining motivation and  emotional  involvement.  Traditional  reading  instruction  often  depends  on memorization  and  repetitive  exercises,  whereas  game-based  learning  combines educational goals with enjoyable activities. This article discusses the importance of game-based reading instruction in early grades, theoretical foundations of play-based learning, types of educational games used in literacy classrooms, benefits of game-based methods, the role of teachers and parents, digital learning opportunities, and challenges  related  to  implementation.  The  article  also  presents  practical recommendations  for  improving  literacy  instruction  through  games  and  interactive learning strategies.